Articuler les niveaux d’activité par les temporalités et les significations - Mélanie Secheppet; Serge Leblanc (Éducation et Socialisation)
One of Horse and Riding French Institut’s missions is the teaching/learning improvement of carriage driving. From this stake, a research’s team was created to study and go with trainers and trainees in a training environment being modified. Articulating epistemic and transformative goals, we picked an enactive anthropology with a socio-historical view to analyze trainers and trainees activities. To describe, understand and explain these activities, we used many scales in order to connect an equestrian culture, an institutional transition and trainers/trainees activities. The results allows to discuss the training-research-innovation articulation and the notions of temporalities.